Electromagnetic survey of cornfield with repeated manure applications - Eigenberg, R.A; Nienaber, J.A (Journal of environmental quality, 1998)
Waste management sites are subject to nutrient buildup from storage, treatment, and repeated application of manure. Methods are needed to quickly assess a site or field location to survey nutrient levels and estimate risk potential. Electromagnetic (EM) conductivity methods have been shown to be sensitive to areas of high nutrient levels (Eigenberg et al., 1996) and offer promise to provide field assessments. In this report, high density electromagnetic field mapping is described as a method to isolate and detect areas of nutrient buildup in a cornfield receiving waste management research treatments. Various manure and compost rates have been applied to this research field for replacement of commercial fertilizer with the treatment assignments remaining identical over a 4-yr period. Electromagnetic conductivity measurements were able to differentiate (P < 0.0001) the N check treatment (commercial application rate) vs. manure applied at the recommended P rate, compost applied at the P rate, and compost applied at the N rate. The N check treatment and the manure applied at the N rate treatment resulted in nearly identical mean values for EM readings and were not statistically distinguishable. Analysis of soil cores (NO3, Cl, P, K, SO4, NH4, Na, electrical conductivity, and soil moisture content) randomly located within each treatment were compared to EM readings at the same locations. The Pearson correlation coefficients revealed strong (P = 0.02 or better) correlations for all constituents except NH4 (P = 0.308). Treatment effects were significant (P = 0.05) for all soil constituents except NH4 and water content.